2016
DOI: 10.1002/bio.3149
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent carbon nanoparticles from Citrus sinensis as efficient sorbents for pollutant dyes

Abstract: Here, we report a simple, green and economic process for the synthesis of highly fluorescent carbon nanoparticles (CPs) through low-temperature carbonization of a fruit waste, Citrus sinensis peel. This approach allows the large-scale production of aqueous CPs dispersions without any additives and post-treatment processes. The as-prepared CPs were of small particle size, exhibited bright blue fluorescence under UV irradiation (λ = 365 nm) with excellent colloidal stability in water. The chemical composition, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Furthermore, TEM revealed the morphology of all FNP types, which display as dot shapes with an average diameter of 4 to 20 nm and have a dark surface color, demonstrating successful surface passivation. The lattice separation of the materials (approximately 0.290 to 0.308 nm) confirmed the graphene carbon structures indicating internalized carbon particles (Figure c and d) . The prepared CDs derived from natural sources have tunable absorption and fluorescence emission patterns, indicating the promising possibility for sustainability in bio‐probe applications.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Furthermore, TEM revealed the morphology of all FNP types, which display as dot shapes with an average diameter of 4 to 20 nm and have a dark surface color, demonstrating successful surface passivation. The lattice separation of the materials (approximately 0.290 to 0.308 nm) confirmed the graphene carbon structures indicating internalized carbon particles (Figure c and d) . The prepared CDs derived from natural sources have tunable absorption and fluorescence emission patterns, indicating the promising possibility for sustainability in bio‐probe applications.…”
Section: Resultsmentioning
confidence: 64%
“…The C-FNPs and P- (Figure 3c and d). [25][26][27][28] The prepared CDs derived from natural sources have tunable absorption and fluorescence emission patterns, indicating the promising possibility for sustainability in bio-probe applications.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that CDs derived from orange peels emitted blue fluorescence. [ 5–8,10,11 ] However, CPs obtained in this study emitted green/yellow fluorescence when ddH 2 O only was used as reaction solvent (Figure 1a). These inconsistent results might be due to different composition of the peels obtained from various oranges cultivars.…”
Section: Resultsmentioning
confidence: 77%
“…Step 2: surface modification (Figure 10(a)). The PL maximum for CDs commonly appears in the blue and green region of the spectra (Figure 10(b)) [41]. PL behavior of CDs can be controlled by varying the initial precursors and synthetic methodologies and by surface engineering [42].…”
Section: Absorption Spectroscopy (Uv-vis)mentioning
confidence: 99%
“…(a) PL spectra of CDs with variation of excitation wavelengths (λ ex ); (b) excitation and PL emission spectra of CDs in the blue-green region (reproduced with permission from[41]). …”
mentioning
confidence: 99%